A space of one’s own; recreating educational environments based on student opinions at Angeredsgymnasiet - Nathorst Westfelt, Astrid (My University, 2024)
As the climate crisis worsens, the need to transition towards a more sustainable society has never been more evident or more urgent. In a suburb of Gothenburg, Sweden, the secondary school Angeredsgymnasiet faces demolition as the building is nearing the end of its life span. This demolition, however, can not be considered a sustainable choice, neither from a social, ecological or economic perspective. This thesis aimed to show how participatory work can be used in transformative design processes to identify challenges and motivate design which was done through the example of Angeredsgymnasiet. The thesis analyzed four participatory reference projects previously conducted in cooperation with students at Angeredsgymnasiet. Literary analysis and case studies were used as complimentary sources. The research found that although the building faces some technical challenges the main concerns were the experience of safety, the lack of high quality spaces for breaks, and a lack of identity and creativity in the design. The identified challenges were addressed in a transformative design proposal in which functions were redistributed to activate the whole building and create natural meeting places. Some of the courtyards were transformed to interior boulevards, creating a dynamic space for social interaction, while existing corridors were widened to create calm streets. The learning spaces were placed in modules framed by the streets and boulevards, providing flexible environments for all kinds of students. Finally, identity was created through the addition of new materials, furntiure, and light fixtures. The result is a school were students are free to relax and be themselves - a space of their own
Keywords: secondary school design, transformation, participation, education